Establishing a green biodesulfurization process for iron ore concentrates in stirred tank and leaching column bioreactors using Acidithiobacillus thiooxidans - Bobadilla-Fazzini, Roberto A.; Poblete-Castro, Ignacio (Frontiers in Bioengineering and Biotechnology, 2023)
The presence of sulfur impurities in complex iron ores represents a significant challenge for the iron mining and steel-making industries as their removal often necessitates the use of hazardous chemicals and energy-intensive processes. Here, we examined the microbial and mineralogical composition of both primary and secondary iron concentrates, identifying the presence of Sulfobacillus spp. and Leptospirillum spp., while sulfur-oxidizing bacteria were absent. We also observed that these concentrates displayed up to 85% exposed pyrrhotite. These observations led us to explore the capacity of Acidithiobacillus thiooxidans to remove pyrrhotite-sulfur impurities from iron concentrates. Employing stirred tank bioreactors operating at 30°C and inoculated with 5·106 (At. thiooxidans cells mL-1), we achieved 45.6% sulfur removal over 16 days. Then, we evaluated packed leaching columns operated at 30°C, where the At. thiooxidans enriched system reached 43.5% desulfurization over 60 days. Remarkably, sulfur removal increased to 80% within 21 days under potassium limitation. We then compared the At. thiooxidans-mediated desulfurization process, with and without air supply, under potassium limitation, varying the initial biomass concentration in 1-m columns. Aerated systems facilitated approximately 70% sulfur removal across the entire column with minimal iron loss. In contrast, non-aerated leaching columns achieved desulfurization levels of only 6% and 26% in the lower and middle sections of the column, respectively. Collectively, we have developed an efficient, scalable biological sulfur-removal technology for processing complex iron ores, aligning with the burgeoning demand for sustainable practices in the mining industry.